Individual differences in structural priming in bilingual and monolingual children: the influence of perspective-taking - Joyce L. van Zwet; Sharon Unsworth (Language and Cognition, 2024)
When speaking or writing, people tend to re-use the syntactic structures they recently encountered (structural priming). Individuals differ in the extent to which they are primed (primeability). Previous research has suggested that perspective-taking, that is, the ability to imagine the feelings, thoughts and perceptions of others, predicts the magnitude of priming in adults. The present study investigates if this also holds for monolingual and bilingual children. We primed the possessive structure in monolingual Dutch children and bilingual children with varying L2s. There was individual variation in children’s primeability in both groups. For both monolinguals and bilinguals, we found that the better children were at perspective-taking, the more likely they were to be primed. Dutch language proficiency also influenced children’s primeability: higher language proficiency resulted in more priming in both groups. The findings suggest that structural priming serves a social function which is mediated by perspective-taking abilities.